2020
DOI: 10.1016/j.dnarep.2020.102860
|View full text |Cite
|
Sign up to set email alerts
|

Expanding molecular roles of UV-DDB: Shining light on genome stability and cancer

Abstract: UV-damaged DNA binding protein (UV-DDB) is a heterodimeric complex, composed of DDB1 and DDB2, and is involved in global genome nucleotide excision repair. Mutations in DDB2 are associated with xeroderma pigmentosum complementation group E. UV-DDB forms a ubiquitin E3 ligase complex with cullin-4A and RBX that helps to relax chromatin around UV-induced photoproducts through the ubiquitination of histone H2A. After providing a brief historical perspective on UV-DDB, we review our current knowledge of the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 98 publications
3
26
0
Order By: Relevance
“…To this end our laboratory recently described a role for UV-damaged DNA binding protein (UV-DDB) in the BER of 8-oxoguanine [59]. UV-DDB is a heterodimeric protein, consisting of DDB1 and DDB2 subunits, and acts as first responder to UV-damage during nucleotide excision repair (NER) [60]. After UV-damage, UV-DDB forms an E3-ubiqutin ligase complex with Cul4A and RBX to ubiquitinate histones and remodel the chromatin to increase lesion accessibility for downstream repair proteins [61].…”
Section: Discussionmentioning
confidence: 99%
“…To this end our laboratory recently described a role for UV-damaged DNA binding protein (UV-DDB) in the BER of 8-oxoguanine [59]. UV-DDB is a heterodimeric protein, consisting of DDB1 and DDB2 subunits, and acts as first responder to UV-damage during nucleotide excision repair (NER) [60]. After UV-damage, UV-DDB forms an E3-ubiqutin ligase complex with Cul4A and RBX to ubiquitinate histones and remodel the chromatin to increase lesion accessibility for downstream repair proteins [61].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the binding of UV-DDB seems to precede the activity of ATP-mediated chromatin remodelers ( 53 , 54 ). More recently, as discussed in the last section, our group has demonstrated that the oxidative base damage 8-oxoG, which only causes a mild helix distortion, is recognized by UV-DDB in naked duplex DNA, as well as in living cells ( 55 , 56 ). The relatively mild nucleosome distortion caused by CPD and 8-oxoG is analogous to cyPu.…”
Section: Could Cyclopurine Deoxynucleosides Explain Neurodegenration mentioning
confidence: 91%
“…It should be noted that previous studies missed that UV-DDB was able to discriminate between non-damaged DNA and DNA containing 8-oxoG ( 96 ). We have found that the presence of magnesium helps increase damage specificity by greatly decreasing binding to non-damaged DNA duplexes ( 55 , 56 ). EMSA assays conducted in the presence of 5 mM Mg 2+ showed that UV-DDB preferentially bound abasic sites, CPD and 8-oxoG, with equilibrium dissociation constants, K d , of 3.9, 30 and 160 nM, respectively, with high specificity as compared to undamaged DNA ( K d = 1108 nM) ( 55 , 56 ).…”
Section: A New Role Of Uv-ddb In the Removal Of 8-oxogmentioning
confidence: 96%
See 2 more Smart Citations